2013
DOI: 10.4103/0301-4738.119347
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of prenatal and postnatal risk factors of retinopathy of prematurity in a tertiary care hospital in South India

Abstract: Context:Recent advances in neonatology have influenced the incidence and severity of ROP in a dichotomous fashion.Aims:To determine the incidence of ROP and to analyse its risk factors.Settings and Design:Prospective clinical case series.Materials and Methods:282 preterm infants with birthweight < 1500g and/or gestational age ≤ 32 weeks and also those with gestational age > 32 weeks, with birthweight between 1500-2000 g, who were at risk for ROP were selected. Weight gain proportion was measured as weight at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 14 publications
(18 reference statements)
2
7
0
Order By: Relevance
“…328 These results have been replicated in multiple subsequent studies, both for the risk of incident ROP and of treatment-requiring ROP. 6,10,11,13,14,17,18,21,47,57,65,75,77,94,102,109,114,122,125,135,138,143,147,152,157,174,202,204,216,228,231,233,236,240,246,255,263,266,271,276,282,283,285,308,311,312,315,335,337,348,362,367,371,373,378,391,398,405,406,410,412,418…”
Section: Major Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…328 These results have been replicated in multiple subsequent studies, both for the risk of incident ROP and of treatment-requiring ROP. 6,10,11,13,14,17,18,21,47,57,65,75,77,94,102,109,114,122,125,135,138,143,147,152,157,174,202,204,216,228,231,233,236,240,246,255,263,266,271,276,282,283,285,308,311,312,315,335,337,348,362,367,371,373,378,391,398,405,406,410,412,418…”
Section: Major Risk Factorsmentioning
confidence: 99%
“…269 IVH occurs in 25–30% of all preterm infants <1,500 g. 344 For unclear reasons, IVH has repeatedly been associated with ROP and appears in many of the articles reviewed. 12,14,23,35,58,68,76,122,174,220,235,266,272,311,336,337,387,395,398,405,414,415 An epidemiologic analysis of 2,950 infants in Turkey revealed that any IVH was associated with greater risk of ROP. 23…”
Section: Alternative Risk Factorsmentioning
confidence: 99%
“…The incidence of ROP reported in India varies between 2.4% and 42% among screened infants, with study population varying from less than 32 to 34 weeks and birth weight less than 1,500 to 2,000 g. [4][5][6][7][8][9][10][11][12][13][14][15] The special neonatal care units (SNCUs), which are the cornerstone of sick and LBW neonates in India report a 15% incidence of sight-threatening (ST ROP), that is, ROP requiring intervention. 6 Globally the reported incidence is between 15.2% and 42.7%.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since ROP was first described over 75 years ago, there have been a conglomerate of papers that identify distinct putative risk factors and interventions to prevent ROP. [3][4][5][6][7][8][9][10][11][12][13] Previous studies from the authors' reported various risk factors of which significant ones were prematurity, low birth weight (LBW), and lack of antenatal steroids. 14,15 Multiple We hypothesized that clinical stability provided by KMC would lead to a reduction in any stage of ROP and severity of ROP in neonates who receive effective KMC during a hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…There is conflicting evidence on whether multiple pregnancy increases the risk of ROP[26] with some studies finding no difference[2728] whereas others have reported an increased risk. [2930] We did not find a significant difference in our study.…”
Section: Discussionmentioning
confidence: 99%